Contemporary Relevance of Anne Moody, Black Studies and Imprisoned Black Intellectual Thought - Norris, Adele N.; Conley, Glen; Cooper, Garrick; Martin, Jessica (Journal of Critical Race Inquiry)

(untitled) (Queen's University, 2025)
Anne Moody’s 1968 autobiographical text, Coming of Age in Mississippi, is receiving increased interest during this current moment of legislated anti-Blackness, most observable in the removal/outlawing of Black history and thought. Moody’s early life in the Deep South during the 1940s-1950s and as a foot soldier in the Civil Rights Movement inform how we understand the continuity of anti-blackness and racial terror. Glen Conley, an imprisoned citizen, examines and teaches Anne Moody within a Mississippi prison context. While her book is used across several academic disciplines, the study of Moody within the prison context is not well known. Conley’s political poetry explores Moody’s life and text, bringing renewed attention to themes of Black mental health, survival, and resistance under a harsh U.S. Southern regime. Using a prison-praxis framework, this paper centers the knowledge production from the civically dead (imprisoned population), which allows for broader insights into themes of racialized confinement, criminalization and surveillance. Thus, this essay situates Conley’s scholarship within the lineage of Black imprisoned radical tradition where he draws attention to Moody’s prescient voice during a political climate of overt forms of legislated anti-Blackness and systemic erasure.